Static compartmentalisation vs. dynamic molecular interaction – - Leonie Johann; Jorge Groß; Fredrik Karl Henry Rusk (Nordina: Nordic Studies in Science Education)
Framed by the Model of Educational Reconstruction and Conceptual Metaphor Theory, this case study explores upper secondary students’ conceptions about cell membrane biology through qualitative analysis of semi-structured interviews. The study aims to examine how this topic may be taught to help students make informed decisions about, for example, health and lifestyle choices. Findings suggest that students ‘conceptions are often rooted in everyday experiences, such as perceiving cell membranes as static structures that serve to protect cells. Without explicit clarification, these conceptions may hinder students ‘understanding of the dynamic role cell membranes play in the dynamic organisation of multicellular organisms. To address these challenges, we propose elementary concepts and learning goals to support a gradual learning process. This approach enables upper secondary students to link molecular interactions within cell membranes to their functional roles in biological compartmentalisation and coordination – crucial processes for the maintenance and existence of life.